The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1310/hpj4706-451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vancomycin Dosing and Monitoring in Adult Medicine Patients

Abstract: Purpose To assess the clinical impact of a vancomycin dosing protocol and monitoring tool on initial dose, dosing interval, and trough concentrations in adult medicine patients. Methods This was a retrospective chart review of adult medicine patients who received at least one dose of vancomycin and were admitted during the pre-implementation period, February 1 to April 2009, or during the post-implementation period, June 1 to October 31, 2009. All outcomes for patients in the pre-implementation group were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…In contrast, our nomogram allows the clinician to choose the appropriate trough goal, 10–15 mcg/mL or 15–20 mcg/mL, based on the patient's indication for therapy. Our results are comparable to those in the Devabhakthumi et al study, in which 44% versus 45% of subjects were in the therapeutic range, respectively, and this may be due to our similar inclusion criteria which was very broad with few exclusion criteria, making the nomograms broadly applicable [11]. Our results are lower than those seen in the Kullar et al study, 44% versus 58%, respectively, and may be due to the fact that the patients included in the Kullar et al study were generally stable.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast, our nomogram allows the clinician to choose the appropriate trough goal, 10–15 mcg/mL or 15–20 mcg/mL, based on the patient's indication for therapy. Our results are comparable to those in the Devabhakthumi et al study, in which 44% versus 45% of subjects were in the therapeutic range, respectively, and this may be due to our similar inclusion criteria which was very broad with few exclusion criteria, making the nomograms broadly applicable [11]. Our results are lower than those seen in the Kullar et al study, 44% versus 58%, respectively, and may be due to the fact that the patients included in the Kullar et al study were generally stable.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison to the nomogram developed by Devabhakthumi et al, our nomogram is similar in design, utilizing weight to determine the vancomycin dose and creatinine clearance to determine the dosing interval [11]. However, the Devabhakthumi nomogram did not differentiate between obese and nonobese patients and also did not separate trough goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are similar to previous first‐world studies that reported therapeutic trough concentrations of 42% to 45% . Achievement of therapeutic trough concentrations was 21% higher when computerized TDM procedures were adhered to.…”
Section: Discussionmentioning
confidence: 99%